V-Model Adaptation for Space Systems in Light of the ECSS Standard - Moraes, Regina; Basso, Tania; Martins, Eliane (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS); 2021: Anais do II Workshop on Validation and Verification of Future Cyber-physical Systems, 2021)
A challenge in the space domain is to adapt the V&V (Verification and Validation) process to answer to the growing importance of embedded software and still comply with international standards. This work presents an analysis of the ECSS (European Cooperation for Space Standardization) standard to allow the adaptation of the well-known V-Model for Cyber-Physical System (CPS), particularly for space systems. The result is a complete model capable of representing the physical and software segments, as well as positioning ECSS revisions throughout the system development and its testing/validation tasks.